EVALUASI IMPELEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM & BUDI PEKERTI SMA NEGERI 12 MERANGIN - Cantika Mukti Andini; Dwinar Maricha Anggraini; Siti Zakia Fuadatinnur; Ahmad Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of the Independent Curriculum in the subjects of Islamic Religious Education and Character Education at SMA Negeri 12 Merangin. The evaluation focuses on three main aspects, namely planning, implementation, and implementation results. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation of the principal, vice principal for curriculum, Islamic Religious Education teachers, and grade XI Phase F1 students. The results of the study indicate that learning planning has referred to the principles of the Independent Curriculum through the preparation of ATP, CP, and teaching modules that integrate the values ​​of the Pancasila Student Profile. The implementation of learning shows a shift from a teacher-centered to a student-centered approach, although some teachers are still in the adaptation stage. Evaluation of the results shows an increase in student participation and understanding of Islamic Religious Education material, but obstacles are still found such as limited time, teacher readiness, and adaptation to the use of technology. This study concludes that the implementation of the Independent Curriculum at SMA Negeri 12 Merangin has gone quite well, but further assistance and training are needed to optimize the implementation of the curriculum.